Intellectual capital and organisational performance in Malaysian knowledge-intensive SMEs - Khalique, Muhammad; Bontis, Nick; Shaari, Jamal Abdul Nassir; Yaacob, Mohd Rafi; Ngah, Rohana (2018)
This study was designed to test and validate the integrated intellectual capital model by examining the relationship between intellectual capital and organisational performance of small and medium enterprises (SMEs) operating in the electrical and electronics manufacturing sectors in Malaysia. Data was collected through a validated survey instrument administered on a sample of 237 respondents from targeted SMEs. Cronbach’s alpha and confirmatory factor analysis were used to examine the reliability and validity of the research instrument. Structural equation modelling was used to test the proposed research hypotheses. The results demonstrate that human capital, customer capital, structural capital, social capital, technological capital and spiritual capital are crucial components of intellectual capital and all link to organisational performance. Although there are limitations to measuring intellectual capital quantitatively, this study provides further insight into the relationship between intellectual capital and organisational performance within a developing nation. The limitations of the study include a limited scope of generalisability.